The Chloroplast Genome of Passiflora edulis (Passifloraceae) Assembled from Long Sequence Reads: Structural Organization and Phylogenomic Studies in Malpighiales - Cauz-Santos, Luiz A.; Munhoz, Carla F.; Rodde, Nathalie; Cauet, Stephane; Santos, Anselmo A.; Penha, Helen A.; Dornelas, Marcelo C.; Varani, Alessandro M.; Oliveira, Giancarlo C. X.; Bergès, Hélène; Vieira, Maria Lucia C. (Frontiers in Plant Science, 2017)
The family Passifloraceae consists of some 700 species classified in around 16 genera. Almost all its members belong to the genus Passiflora. In Brazil, the yellow passion fruit (Passiflora edulis) is of considerable economic importance, both for juice production and consumption as fresh fruit. The availability of chloroplast genomes (cp genomes) and their sequence comparisons has led to a better understanding of the evolutionary relationships within plant taxa. In this study, we obtained the complete nucleotide sequence of the Passiflora edulis chloroplast genome, the first entirely sequenced in the Passifloraceae family. We determined its structure and organization, and also performed phylogenomic studies on the order Malpighiales and the Fabids clade. The P. edulis chloroplast genome is characterized by the presence of two copies of an inverted repeat sequence (IRA and IRB) of 26,154 bp, each separating a small single-copy (SSC) region of 13,378 bp and a large single-copy (LSC) region of 85,720 bp. The annotation resulted in the identification of 105 unique genes, including 30 tRNAs, 4 rRNAs and 71 protein coding genes. Also, 36 repetitive elements and 85 SSRs (microsatellites) were identified. The structure of the complete cp genome of P. edulis differs from that of other species because of rearrangement events detected by means of a comparison based on 22 members of the Malpighiales. The rearrangements were three inversions of 46,151 bp, 3,765 bp and 1,631 bp, located in the LSC region. Phylogenomic analysis resulted in strongly supported trees, but this could also be a consequence of the limited taxonomic sampling used. Our results have provided a better understanding of the evolutionary relationships in the Malpighiales and the Fabids, confirming the potential of complete chloroplast genome sequences in inferring evolutionary relationships and the utility of long sequence reads for generating very accurate biological information.